2007
DOI: 10.1017/s1461145706007425
|View full text |Cite
|
Sign up to set email alerts
|

Durability of antidepressant response to vagus nerve stimulation (VNS)

Abstract: This study characterized the durability of improvement in patients who responded early or late while receiving vagus nerve stimulation (VNS). In both a pilot and pivotal study, patients were identified who had at least a 50% reduction in symptom scores 3 months (early responders) or 12 months (late responders) after starting VNS. Probabilities were determined for maintenance of response at 12-month and 24-month time-points. Consistency of improvement throughout the 24-month study period was evaluated, testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 28 publications
(26 reference statements)
6
62
0
1
Order By: Relevance
“…After 12 months of VNS, both response and remission rates were about double those at 3 months. In this cohort, it was found that if patients responded beneficially to VNS after either 3 or 12 months of treatment, then efficacy was maintained for up to 24 months (Sackeim et al, 2007).…”
Section: Introductionmentioning
confidence: 84%
“…After 12 months of VNS, both response and remission rates were about double those at 3 months. In this cohort, it was found that if patients responded beneficially to VNS after either 3 or 12 months of treatment, then efficacy was maintained for up to 24 months (Sackeim et al, 2007).…”
Section: Introductionmentioning
confidence: 84%
“…It is instructive to note, however, that many responders in the VNS clinical trials maintained their initial positive response through 24 months. 49 Although remission of depressive symptoms has not been associated with an increase in manic symptoms, this possibility in the future cannot be ruled out.…”
Section: Limitations and Conclusionmentioning
confidence: 96%
“…Open-label long-term response and remission rates were higher (27% response rate and 16% remission rate after 12 months of stimulation) and statistically significantly greater than 12-month naturalistic outcomes in a nonrandomized treatment-as-usual comparison group not receiving VNS (13% response rate, 7% remission rate) (31)(32)(33). In longer-term follow-up studies, 21%-50% of patients who responded to VNS failed to maintain at least a 40% decrease in baseline depression severity over 1-2 years (34,35). In an open-label European cohort, 56% of patients who had responded during 1 year of VNS relapsed within the next year (36).…”
Section: Current Treatment Approachesmentioning
confidence: 99%